Steamboats COLUMBIAN and ELDORADO starting from Dawson on a race to Whitehorse Rapids on the Yukon River, Yukon Territory, July 4, 1899. - Hegg & Co.
Caption on image: "Canadian Development Co.'s str. "Columbian" and the Yukon Flyer Line Co.'s "Eldorado" starting from Dawson July 4th 99 on a race to White Horse Rapids." PH Coll 246.108 [Meed journal: "Canadian Development Co.'s steamer "Columbian" and the Yukon Flyer Line Co.'s "Eldorado" starting from Dawson July 4,1899 on a race to White Horse Rapids."] To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number